The landscape of somatic mutation in normal colorectal epithelial cells - Lee-Six, Henry; Olafsson, Sigurgeir; Ellis, Peter; Osborne, Robert J.; Sanders, Mathijs A.; Moore, Luiza; Georgakopoulos, Nikitas; Torrente, Franco; Noorani, Ayesha; Goddard, Martin; Robinson, Philip; Coorens, Tim H. H.; et al. (Nature (London), 2019)
The colorectal adenoma–carcinoma sequence has provided a paradigmatic framework for understanding the successive somatic genetic changes and consequent clonal expansions that lead to cancer 1 . However, our understanding of the earliest phases of colorectal neoplastic changes—which may occur in morphologically normal tissue—is comparatively limited, as for most cancer types. Here we use whole-genome sequencing to analyse hundreds of normal crypts from 42 individuals. Signatures of multiple mutational processes were revealed; some of these were ubiquitous and continuous, whereas others were only found in some individuals, in some crypts or during certain periods of life. Probable driver mutations were present in around 1% of normal colorectal crypts in middle-aged individuals, indicating that adenomas and carcinomas are rare outcomes of a pervasive process of neoplastic change across morphologically normal colorectal epithelium. Colorectal cancers exhibit substantially increased mutational burdens relative to normal cells. Sequencing normal colorectal cells provides quantitative insights into the genomic and clonal evolution of cancer. Genome sequencing of hundreds of normal colonic crypts from 42 individuals sheds light on mutational processes and driver mutations in normal colorectal epithelial cells.